PEMBUATAN COMPANY PROFILE DALAM BENTUK WEBSITE (Studi Kasus : PT Prima Rasa Citratama) - Fajarsodik, Ahmad; Savitri, Peti (Universitas Sangga Buana, 2024)
This research is directed towards the design and implementation of a corporate profile website for PT. Prima Rasa Citratama, employing the PHP programming language and MySQL database. The study involves a comprehensive analysis of system requirements, meticulous conceptual design, website implementation, and functional testing utilizing Black Box and White Box methods. The company profile includes history, visual identity, and PT. Prima Rasa's scope of work, with the goal of providing relevant information to users. The system is built to enhance marketing and facilitate remote sales transactions. Through requirement analysis, conceptual and physical system designs were created. Conceptual design involves Use Case, Activity, Class, and Sequence diagrams, while physical design includes user interface (UI) and input/output data form designs. Implementation results show that the website can be accessed smoothly and meets functional and non-functional requirements. Black Box and White Box testing successfully verified system functions and components. Questionnaire results indicate user satisfaction with the appealing layout, menu flexibility, and user-friendly nature of the website. The satisfaction score reached 91.14%. Thus, the corporate profile website for PT. Prima Rasa Citratama contributes positively to enhancing company visibility, disseminating product information, and facilitating online transactions.